Developing Scientific Oral Presentation Competence focusing on Question-and-Answer Sessions of High-Ability Science Students in Thailand - Arwae, Sophia; Soontornwipast, Kittitouch (LEARN Journal: Language Education and Acquisition Research Network, 2022)
This study is aimed at developing students' scientific oral presentation competence and competence in question-and-answer sessions, through the scientific presentation instruction: focus on question-and-answer sessions (SPIQA). The SPIQA contained coping strategies for question-and-answer sessions, communication strategies, impromptu speech strategies, and Socratic questioning techniques. Also, this study explored the students' opinions toward the SPIQA. The participants were 35 high-ability science high school students. The impacts of the SPIQA on scientific oral presentation competence and competence in question-and-answer sessions were assessed through pre- and post- scientific oral presentation tests. The participants’ opinions were obtained from students' learning journals, questionnaires, and interviews. Further information was extracted from the questionnaires through examination of teacher notes and journals. The findings show significant improvement in students’ scientific oral presentation test scores, implying that a teaching pedagogy made up of a combination of different sets of strategies is effective. Qualitative results indicate that students had positive opinions of the strategies instruction, and that they realized the importance of oral presentation competence and competence in question-and-answer sessions in relation to their future education needs and career goals. In further studies, it is therefore recommended to raise students' awareness of strategy use for solving communication problems.